The relationship between domestic violence and women’s sexual function in the city of Puntianak - Lidia Hastuti; Suriadi; Tutur Kardiatun; Titan Ligita (Universiti Kebangsaan Malaysia, 2011)
The increasing number of domestic violence every year causes many health problems mainly women’s reproductive health. This violence may influence the sexual life in their families, especially women’s sexual function. It is known that the sexuality is as a part of family’s life. The fulfilled family will guarantee their pleasurable sexual life. At this point, no research has been conducted to investigate whether there is a relationship between the domestic violence and the sexual function in Pontianak. The research was planned to investigate the relationship between domestic violence and women’s sexual function in Pontianak.